MULTILATERAL DIMENSIONS IN TALENT MANAGEMENT AND EMPLOYEES’ TURNOVER INTENTIONS IN MANUFACTURING INDUSTRIES, SOUTH-WEST, NIGERIA. - BALOGUN, Adetoun; Akintayo , Dayo (Annals of Spiru Haret University. Economic Series, 2024)
The importance of employees to manufacturing industries cannot be overemphasised as they contribute to the industries’ performance and the consequent impact on the nation’s economy. This study, therefore, investigated the contributions of talent management strategies (human resource planning, recruitment and selection, employee development, employee retention, employee health and safety management, and employee performance appraisal) to employees’ turnover intentions in manufacturing industries in South-West Nigeria. The study employed a descriptive survey research design. The target population of the study comprised 3,172 staff working in six manufacturing industries in South-West Nigeria. The study made use of stratified and simple random sampling techniques to select 952 respondents. Two research instruments, the Integrated Talent Management Strategies Questionnaire (ITMSQ) and the Employees’ Turnover Intentions Questionnaire (ETIQ), were validated, and their reliability was ascertained. Two research questions were raised, and two hypotheses formulated were analysed with inferential statistics. The findings reveal a low level of employees’ turnout intentions, the adoption at a high rate of all examined talent management strategies, and significantly combined and relative contributions of talent management strategies to employees’ turnout intentions. Recommendations made include organisations’ need to adopt more talent management strategies, regularly evaluate the effectiveness of integrated talent management practices adopted, and improve retention programmes based on the identified integrated talent management strategies that contribute significantly to turnover employees’ turnout intention. Keywords: Talent Management Strategies and Employees Turnover Intentions JEL Classification: L1